ON SOME TYPES OF GENERALIZED T*-COMPACT FUNCTION IN TOPOLOGICAL SPACES - Ibrahem, Afrah Mohammad; Yassen, Rana Bahjat (MAGISTRA, 2011)
In this paper, we introduce a new topological space called generalized ô*-compact space, and studysome properties about it .Also we introduce a new types of compact functions called the generalized ?*-compactfunction and the generalized ?**-compact function, and study the relation among them and another functions.